Customer Experience Monitoring: A Study of Zambian Banks - Simwanza , Martha Mumbi; Awolusi, Olawumi Dele (Journal of Education and Vocational Research, 2020)
The fast growing level of competitiveness and fundamental amendments in the world of business especially in the banking sector nowadays are pushing firms and for that matter banks to implement a customer-based strategy, which proves the importance of customer experience monitoring constructs such as customer experience and satisfaction, quality of service, and customer loyalty in explaining a bank’s performance. Consequently, this study seeks to develop and empirically test customer experience monitory and evaluation and also to study the influences of service quality, customer satisfaction, and customer loyalty in the Zambian banking industry. A survey was conducted with banking customers on many validated questions, based on which we got 107 valid responses. The data was processed to produce the valuable results and Quantitative Data Analysis (QDA), via simple regression analysis and ANOVA. The findings and analysis of data shows that quality of service provided and customer satisfaction are important when monitoring the experience of customers based on the effects of quality of service and customer loyalty and there returns thereafter. Based on the data analyzed, the study concluded that customer experience has positive impact on customer loyalty and banks must ensure that their customer walk out with good experience by monitoring this periodically to adapt or adjust to current trends. The study also observed a significant relationship between customer satisfaction and customer loyalty. The theoretical and managerial implications of the study confirmed the theoretical framework. Consequently, the following recommendations were contrived: staffs of financial institutions should create a friendly environment with their customers. The Bank’s environment should be conducive, attractive, decent and enabling enough to psychologically assure their customer of the best of service. Also, there should be a routine high quality of service delivered to customers and their views sorted routinely. This may help boost and also add to the value of experience of customers, thus their total satisfaction on the Bank’s service.